Magnetic metal organic framework regulated and controlled by deep eutectic solvent and application of magnetic metal organic framework
The MMIL-101-NH2-DES adsorbent, synthesized with a deep eutectic solvent, effectively removes tetracycline from wastewater with high selectivity and efficiency, overcoming limitations of existing adsorbents by enhancing adsorption capacity and reusability.
Patent Information
- Application Number
- CN202411436436.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-13
AI Technical Summary
Existing methods for removing tetracycline from wastewater are inefficient due to low adsorption capacity and poor reusability of adsorbents, posing environmental risks and microbial resistance challenges.
A magnetic metal organic framework (MMIL-101-NH2-DES) is synthesized using a deep eutectic solvent to enhance adsorption capacity and selectivity, incorporating Fe3O4@PSSMA and 2-aminoterephthalic acid, enabling electrostatic, hydrophobic, and coordination interactions for tetracycline capture.
The MMIL-101-NH2-DES adsorbent achieves a high removal rate of 98.82% in 60 minutes with excellent reproducibility and reusability, addressing environmental concerns and microbial resistance.
Smart Images

Figure CN119119505A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a magnetic metal organic framework, and in particular to a magnetic metal organic framework regulated by a deep eutectic solvent and its application Background Art
[0002] Tetracycline (TC) has a broad-spectrum antibacterial activity and ranks second in the world in terms of usage, accounting for about one-third of antibiotic production and consumption. However, since tetracycline is difficult to be digested and absorbed by humans and animals, the pollutant is usually discharged into the environment in its original form through feces or urine, causing serious environmental pollution. Tetracycline residues can be detected in various water environments and even in drinking water. The abuse of tetracycline poses a significant risk to human health and the environment. The long-term enrichment of tetracycline in the environment may lead to microbial resistance to antibiotics and cause toxicity to native microorganisms in aquatic environments. Therefore, it is very necessary to remove tetracycline from the environment, especially to minimize the adverse effects on aquatic ecosystems.
[0003]
[0004] Due to the variable forms, low biodegradability and complex molecular structure of tetracycline, it is difficult to completely remove tetracycline by traditional wastewater treatment methods. Many researchers have adopted physical and chemical treatment methods such as adsorption, biodegradation, membrane separation, deep oxidation, photocatalytic degradation and electrochemistry to remove tetracycline from aqueous solutions. Among them, the adsorption method has significant advantages such as simple operation, low cost, low energy consumption and no secondary pollution, which is superior to other treatment methods. Many adsorbents have been used to study the removal of tetracycline from aqueous solutions, such as activated carbon, graphene oxide, biochar, clay, sludge, etc. However, due to their relatively low adsorption capacity and poor reusability, their application is limited. How to remove tetracycline from sewage and integrate it into materials is still a problem and challenge worthy of attention. Therefore, it is of great significance to develop a new method for adsorbing tetracycline with high selectivity and high removal rate. Summary of the invention
[0005] Purpose of the Invention
[0006] The invention provides a magnetic metal organic framework MMIL-101-NH2-DES regulated by a deep eutectic solvent. The adsorbent has the characteristics of high selectivity, high removal rate, low cost, high benefit and environmental friendliness when adsorbing tetracycline.
[0007] Technical Solution
[0008] A magnetic metal organic framework regulated by a deep eutectic solvent, characterized in that it is prepared according to the following steps:
[0009] (1) Preparation of deep eutectic solvents (DES)
[0010] Thymol, ethylene glycol and benzyl alcohol were mixed in a molar ratio of 2:2:1, and heated in an oil bath at 80°C for 0.5-2h until a homogeneous clear liquid was formed to obtain DES;
[0011] (2) Preparation of Fe3O4@PSSMA
[0012] FeCl3, ethylene glycol, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, and D-ascorbic acid were added in sequence and stirred, and then NaOH was added and stirred to form a mixture to react in a muffle furnace at 190°C to obtain Fe3O4@PSSMA;
[0013] (3) Preparation of MMIL-101-NH2
[0014] Ultrasonic dispersion of Fe3O4@PSSMA and 2-aminoterephthalic acid in DMF; dissolution of FeCl3·6H2O in DMF; mixing the two and reacting them in a muffle furnace at 80-150°C to obtain MMIL-101-NH2;
[0015] (4) Synthesis of MMIL-101-NH2-DES
[0016] Disperse MMIL-101-NH2 in DES methanol and perform ultrasonication to obtain MMIL-101-NH2-DES.
[0017] The magnetic metal organic framework regulated by the deep eutectic solvent is characterized by being prepared according to the following steps:
[0018] (1) Preparation of DES
[0019] Thymol, ethylene glycol and benzyl alcohol were mixed in a molar ratio of 2:2:1, and heated in an oil bath at 80°C for 0.5-2h until a homogeneous clear liquid was formed to obtain DES;
[0020] (2) Preparation of Fe3O4@PSSMA
[0021] 0.4-0.9g FeCl3, 20-60 mL ethylene glycol, 2-4 g sodium acetate, 0.7-1.5 g poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, 10-20 mg D-ascorbic acid were added in sequence, and stirred for 20-60 min to form a uniform mixture; then 0.4-0.8 g NaOH was added and stirred for 1-2 h until NaOH was completely dissolved; then the whole mixture was reacted in a muffle furnace at 190°C for 6-10 h. After cooling to room temperature, the precipitate was washed three times with 10-50 mL 50% V / V ethanol aqueous solution, and then washed three times with deionized water to obtain Fe3O4@PSSMA, referred to as Fe3O4;
[0022] (3) Preparation of MMIL-101-NH2
[0023] 0.2-0.4 g Fe3O4@PSSMA and 0.2-0.4 g 2-aminoterephthalic acid were ultrasonically treated for 5-20 min and redispersed in 10-40 mL DMF; then, 0.5-1.5 g FeCl3·6H2O was dissolved in 5-20 mL DMF and ultrasonicated for 10-30 min; then the two were mixed and reacted in a muffle furnace at 110°C for 12-36 h; after cooling to room temperature, the precipitate was washed several times with DMF and methanol, and then vacuum dried at 60°C for 24 h to obtain MMIL-101-NH2.
[0024] (4) Synthesis of MMIL-101-NH2-DES
[0025] 100-300 mg MMIL-101-NH2 was dispersed in 10-40 mL methanol containing 2-6 mL DES and ultrasonicated for 1-3 h. The precipitate was washed several times with deionized water and then vacuum dried at 60 °C for 24 h to obtain MMIL-101-NH2-DES.
[0026] As a priority:
[0027] A magnetic metal organic framework regulated by a deep eutectic solvent, characterized in that it is prepared according to the following steps:
[0028] (1) Preparation of DES
[0029] Thymol, ethylene glycol and benzyl alcohol were mixed in a molar ratio of 2:2:1 and heated in an oil bath at 80°C for 1 h until a homogeneous clear liquid was formed to obtain DES;
[0030] (2) Preparation of Fe3O4@PSSMA
[0031] FeCl3, ethylene glycol, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, and D-ascorbic acid were added in sequence and stirred, and then NaOH was added and stirred to form a mixture to react in a muffle furnace at 190°C to obtain Fe3O4@PSSMA;
[0032] (3) Preparation of MMIL-101-NH2
[0033] Fe3O4@PSSMA and 2-aminoterephthalic acid were ultrasonically dispersed in DMF; FeCl3·6H2O was dissolved in 1 DMF; the two were mixed and reacted in a muffle furnace at 110℃ to obtain MMIL-101-NH2;
[0034] (4) Synthesis of MMIL-101-NH2-DES
[0035] Disperse MMIL-101-NH2 in DES methanol and perform ultrasonication to obtain MMIL-101-NH2-DES.
[0036] More specifically:
[0037] A magnetic metal organic framework regulated by a deep eutectic solvent, characterized in that it is prepared according to the following steps:
[0038] (1) Preparation of DES
[0039] Thymol, ethylene glycol and benzyl alcohol were mixed in a molar ratio of 2:2:1 and heated in an oil bath at 80°C for 1 h until a homogeneous clear liquid was formed to obtain DES;
[0040] (2) Preparation of Fe3O4@PSSMA
[0041] 0.65 g FeCl3, 40 mL ethylene glycol, 3.00 g sodium acetate, 1.10 g poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, and 14 mg D-ascorbic acid were added in sequence and stirred for 40 min to form a uniform mixture; then 0.60 g NaOH was added and stirred for 1-2 h until NaOH was completely dissolved; then the whole mixture was reacted in a muffle furnace at 190 ° C for 8 h. After cooling to room temperature, the precipitate was washed three times with 30 mL 50% V / V ethanol aqueous solution, and then washed three times with deionized water to obtain Fe3O4@PSSMA, referred to as Fe3O4;
[0042] (3) Preparation of MMIL-101-NH2
[0043] 0.30 g Fe3O4@PSSMA and 0.31 g 2-aminoterephthalic acid were re-dispersed in 25 mL DMF by ultrasonication for 10 min; then, 0.93 g FeCl3·6H2O was dissolved in 10 mL DMF and ultrasonicated for another 15 min; then the two were mixed and reacted in a muffle furnace at 110 °C for 24 h; after cooling to room temperature, the precipitate was washed several times with DMF and methanol, and then vacuum dried at 60 °C for 24 h to obtain MMIL-101-NH2.
[0044] (4) Synthesis of MMIL-101-NH2-DES
[0045] 200 mg MMIL-101-NH2 was dispersed in 20 mL methanol containing 4.0 mL DES and ultrasonicated for 2 h. The precipitate was washed several times with deionized water and then dried in vacuum at 60 °C for 24 h to obtain MMIL-101-NH2-DES.
[0046] The magnetic metal organic framework regulated by the deep eutectic solvent is used as an adsorbent to adsorb tetracycline.
[0047] Beneficial Effects
[0048] An efficient adsorbent should have excellent adsorption capacity, good dispersibility and easy separation characteristics. Therefore, giving magnetic properties to the adsorbent has become a preferred solution. Although the development of magnetic solid phase extractors has been very extensive, it is still a challenge to improve the magnetic properties of adsorbents, especially composite materials. Poly (4-styrene sulfonic acid-maleic acid) sodium salt (PSSMA) is an anionic polyelectrolyte composed of strongly ionized styrene sulfonic acid segments (SS) and weakly ionized maleic acid segments (MA). The unique chemical structure of PSSMA makes it an excellent ligand and can be used to synthesize various highly charged colloidal nanoparticles. Inspired by this, the present invention selects Fe3O4 wrapped with poly (4-styrene sulfonic acid-maleic acid) sodium salt to increase the magnetism of the magnetic sphere, thereby enhancing the magnetism of the composite material and achieving an easy separation effect to increase the reusability of the material.
[0049] Metal-organic frameworks (MOFs) have been widely used in the removal of environmental pollutants. Despite this, the research on MOFs for tetracycline adsorption is not very sufficient. Amino-functionalized Fe-MOF MIL-101 (MIL-101-NH2) has excellent thermal / chemical stability, high surface area and easy surface functionalization, and has achieved excellent results in the adsorption of dyes, heavy metals and aliphatic aldehydes. Currently, the modification of MOFs with functional reagents is an effective strategy to improve their selectivity and adsorption capacity according to the characteristics of the target analytes. MIL-101-NH2 is particularly suitable as an adsorbent substrate because the 2-aminoterephthalic acid linker in its structure contains amine groups that are easy to functionalize. In addition, MIL-101-NH2 can bind to iron oxide through coordination and exhibits magnetic characteristics that are conducive to separation. MIL-101-NH2 is a well-deserved candidate for adsorbent substrates. In order to make the adsorption strategy develop in the direction of green, sustainable and environmentally friendly, it is particularly important to choose a suitable modification reagent.
[0050] In recent years, researchers have shown great interest in deep eutectic solvents (DES), which are known as "green sustainable solvents" as an alternative to traditional organic solvents. Obviously, DES provides a new idea for studying the functionalization of MIL-101-NH2. DES is a eutectic mixture composed of anions, cations and neutral ligands, and its freezing point is much lower than that of the individual components. The physical and chemical properties of DES are directly affected by the characteristics and structures of hydrogen bond acceptors (HBAs) and hydrogen bond donors (HBDs). For example, by adjusting the carbon chain length of quaternary ammonium halide salts (a common HBA), DES with different hydrophilicity and hydrophobicity can be prepared. At the same time, different halogen atoms can be selected to give DES different electronegativity. In addition, the flexibility and simplicity of DES design can be achieved by adjusting the hydrogen bonding groups in HBD (such as only –COOH or a combination of –COOH and –NH2) and adjusting the number of hydrogen bonding functional groups (such as one or more –COOH).
[0051] Current research focuses on using DES as a "structure-directing agent" for the preparation of various materials. The main purpose of this invention is to utilize the designability of DES and select DES with specific adsorption to tetracycline antibiotics to achieve targeted regulation of MIL-101-NH2, so as to provide a green and sustainable synthesis scheme. In addition, the advantages of DES also include good biodegradability, low cost and low toxicity, which make its synthesis process more in line with the principles of green and sustainable chemistry.
[0052] The present invention uses a ternary DES composed of thymol, ethylene glycol and benzyl alcohol to regulate magnetic MIL-101-NH2 to improve the selective adsorption capacity of tetracycline. This unique synthesis approach utilizes the advantages of DES while retaining the characteristics of MIL-101-NH2. The synthesized MMIL-101-NH2-DES adsorbent has both the large specific surface area and unsaturated reaction sites of MOF and retains multiple reactive functional groups of DES. Tetracycline is captured through multiple interaction mechanisms such as electrostatic interaction, hydrogen bond interaction, π-π stacking and coordination interaction, so that the adsorption capacity and selectivity are improved at the same time. Figure 1 The preparation of MMIL-101-NH2-DES and the whole adsorption process of tetracycline were described, and the effects of temperature and pH on the adsorption capacity were discussed. The adsorption mechanism was deeply explored using FT-IR and XPS characterization methods, and was applied to the removal of tetracycline in wastewater.
[0053] The present invention successfully synthesized a Fe-based MOF functionalized and regulated by DES, and achieved the selective removal of tetracycline antibiotics in sewage. The prepared MMIL-101-NH2-DES adsorbent has excellent adsorption performance for tetracycline, including good adsorption capacity, outstanding anti-interference ability, excellent reproducibility and reusability. The removal rate in a 100 μg / mL tetracycline solution was as high as 98.82% in 60 minutes. Mechanistic studies have shown that MMIL-101-NH2-DES adsorbs tetracycline through electrostatic interaction, hydrophobic interaction, hydrogen bond interaction, coordination interaction and π-π interaction. Using the designability advantage of DES to replace traditional organic solvents to adjust the support material, synthesizing an adsorbent with selective adsorption capacity for the target analyte is in line with the concept of sustainable chemistry. At the same time, the green characteristics of DES also provide a good solution for avoiding secondary pollution in pollutant removal.
[0054] In general, the MMIL-101-NH2-DES adsorbent developed in the present invention has excellent properties such as low cost, high efficiency and environmental friendliness, and provides a promising solution and design idea for long-term and practical sewage remediation. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 , the preparation and overall experimental diagram of MMIL-101-NH2-DES;
[0056] Figure 2 , TEM images of Fe3O4 (A, D), MMIL-101-NH2 (B, E), and MMIL-101-NH2-DES (C, F); particle size distribution of Fe3O4 (G), MMIL-101-NH2 (H), and MMIL-101-NH2-DES (I);
[0057] Figure 3 , EDS scan of MMIL-101-NH2-DES;
[0058] Figure 4 , XRD patterns of Fe3O4, MMIL-101-NH2 and MMIL-101-NH2-DES (A); IR spectra of Fe3O4, MMIL-101-NH2, MMIL-101-NH2-DES and DES (B); TGA curves of Fe3O4, MMIL-101-NH2 and MMIL-101-NH2-DES (C); VSM curves of Fe3O4 and MMIL-101-NH2-DES (D); Zeta diagrams of different nanomaterials (E);
[0059] Figure 5 , N2 adsorption curves of MMIL-101-NH2(A) and MMIL-101-NH2-DES(B);
[0060] Figure 6 、MMIL-101-NH2-DES material amount (A); the effect of adsorption pH (B) and adsorption temperature (C);
[0061] Figure 7 , Four Adsorption isotherm of cycline (A), Langmuir isotherm model fitting (B), Freundlich isotherm model fitting (C); adsorption kinetic curve of tetracycline (D), pseudo-first-order kinetic model fitting (E), pseudo-second-order kinetic model fitting (F);
[0062] Figure 8 , Fe3O4, MIL-101-NH2, MMIL-101-NH2, and MMIL-101-NH2-DES adsorption performance comparison;
[0063] Fig. 9 , interference of various ionic substances on the adsorption capacity of MMIL-101-NH2-DES (A) and selectivity study (B);
[0064] Fig.10 , FT-IR spectra of MMIL-101-NH2-DES before and after adsorption (A); XPS full spectrum (B); Fe 2p XPS spectrum (C); C 1s XPS spectrum (D); N 1s XPS spectrum (E) and O1s XPS spectrum (F);
[0065] Fig.11 , the reusability of MMIL-101-NH2-DES;
[0066] Fig.12 , chromatograms of standard wastewater and after adsorption by MMIL-101-NH2-DES;
[0067] Note: Fe3O4 means Fe3O4@PSSMA. DETAILED DESCRIPTION
[0068] Example 1
[0069] 1. Experimental reagents and chromatographic conditions
[0070] Experimental reagents: ferric chloride (FeCl3), ferric chloride hexahydrate (FeCl3·6H2O), ethylene glycol (EG), D-ascorbic acid, sodium hydroxide (NaOH), methanol, and N,N-dimethylformamide (DMF) were purchased from Sinopharm Chemical Reagent Co., Ltd. (Shanghai, China); poly(4-styrenesulfonic acid-co-maleic acid) sodium salt (PSSMA), 2-aminoterephthalic acid, and sodium acetate were purchased from Aladdin Chemical Co., Ltd. (Shanghai, China); thymol (Thy) was purchased from Sane Chemical Technology Co., Ltd. (Shanghai, China); tetracycline and oxytetracycline (OT) were purchased from MacLean Biochemical Technology Co., Ltd. (Shanghai, China); benzyl alcohol (BnOH) was purchased from Biter Pharmaceutical Technology Co., Ltd. (Shanghai, China). All chemical reagents were analytical reagents without further purification, and the deionized water used was prepared by a laboratory ultrapure water machine (Milli-Q-18.25MΩ*cm system).
[0071] Chromatographic conditions: High performance liquid chromatograph (Shimadzu) equipped with dual LC-20AT pumps, detector is SPD-20A UV detector; chromatographic column: Shimadzu ODS-2 (4.6 mm×150 mm, 5 μm); mobile phase is methanol: 0.05% phosphoric acid solution (30:70, V / V); column temperature: 30°C; injection volume: 10 μL; flow rate: 1.0 mL / min; detection wavelength: 280 nm.
[0072] 2. Preparation of MMIL-101-NH2-DES complex
[0073] (1) Preparation of DES
[0074] DES was synthesized by heating. Weigh 3.05 g of thymol Thy, 0.60 g of ethylene glycol EG and 1.02 g of benzyl alcohol BnOH in a molar ratio of 2:2:1 and heat in an 80°C oil bath for 1 h until a uniform clear liquid is formed. The synthetic route is as follows
[0075] As shown:
[0076]
[0077] (2) Preparation of Fe3O4@PSSMA
[0078] 0.65g FeCl3, 40mL ethylene glycol, 3.00g sodium acetate, 1.10g poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, and 14mg D-ascorbic acid were added to a beaker in sequence, and a uniform mixture was formed after strong magnetic stirring for about 40min. Then 0.60g NaOH was added and stirred for 1-2h until NaOH was completely dissolved. The entire mixture was then transferred to a polytetrafluoroethylene liner and placed in an autoclave, and reacted in a muffle furnace at 190°C for 8h. After cooling to room temperature, the precipitate was washed three times with 30mL 50% (V / V) ethanol aqueous solution, and then washed three times with deionized water to obtain Fe3O4@PSSMA, referred to as Fe3O4.
[0079] (3) Preparation of MMIL-101-NH2
[0080] 0.30 g Fe3O4@PSSMA and 0.31 g 2-aminoterephthalic acid were re-dispersed in 25 mL DMF by ultrasonication for 10 min. After that, 0.93 g FeCl3·6H2O was dissolved in 10 mL DMF and ultrasonicated for another 15 min. The whole mixture was then transferred to a polytetrafluoroethylene liner and placed in an autoclave, and reacted in a muffle furnace at 110 ° C for 24 h. After cooling to room temperature, the precipitate was washed several times with DMF and methanol, and then vacuum dried at 60 ° C for 24 h to obtain MMIL-101-NH2.
[0081] (4) Synthesis of MMIL-101-NH2-DES
[0082] 200 mg of MMIL-101-NH2 was dispersed in 20 mL (containing 4.0 mL of DES) methanol and ultrasonicated for 2 h. The precipitate was washed several times with deionized water and then dried in vacuum at 60°C for 24 h to obtain MMIL-101-NH2-DES.
[0083] 3. Optimization of adsorption conditions
[0084] The effects of adsorbent dosage, pH and temperature on the adsorption of tetracycline were investigated, and the optimal adsorbent dosage, adsorption pH and adsorption temperature were obtained.
[0085] (1) Optimization of adsorbent dosage
[0086] 1.0, 2.0, 3.0, 4.0, 5.0 mg of MMIL-101-NH2-DES were weighed, added to 4.0 mL of 100.0 μg / mL tetracycline solution, and the mixture was placed in an ultrasound chamber and sonicated for 2 h at room temperature. After adsorption was completed, the material was separated using an external magnetic field. HPLC analysis was performed to determine the tetracycline concentration in the supernatant. The adsorption capacity was calculated according to formula (1).
[0087] Q=(C0-C e )V / W#(1)
[0088] (2) Adsorption pH optimization
[0089] The effect of tetracycline solution on its adsorption capacity under pH 3.0-9.0 conditions was studied. 100.0 mL of tetracycline solution with a concentration of 200.0 μg / mL was prepared. 21 portions of MMIL-101-NH2-DES were weighed, 3 portions for each pH, each portion was about 3.0 mg, and the material was dispersed in 2.0 mL of tetracycline solution and 2.0 mL of PB buffered saline solution of different pH. Then it was put into ultrasound, sonicated at room temperature for 2 hours, and then separated by an external magnetic field. The supernatant was taken, filtered with a 0.22 μm organic membrane, and analyzed by HPLC to determine the tetracycline concentration in the supernatant. Its adsorption capacity was calculated according to formula (1).
[0090] (3) Adsorption temperature optimization
[0091] The effect of temperature on the adsorption capacity of tetracycline was studied. 100.0 mL of tetracycline solution with a concentration of 200.0 μg / mL was prepared. 18 portions of MMIL-101-NH2-DES were weighed, 3 portions at each temperature gradient, and each portion was about 3.0 mg. 2.0 mL of tetracycline solution and 2.0 mL of PB buffer solution with a pH of 8.0 were added, and then placed in an ultrasound chamber and ultrasound was performed for 2 h at 25°C, 30°C, 35°C, 40°C, 45°C, and 50°C. The material was then separated by an external magnetic field, the supernatant was taken, and HPLC analysis was performed to determine the tetracycline concentration in the supernatant, and the adsorption capacity of MMIL-101-NH2-DES at different temperatures was calculated using formula (1).
[0092] 4. Study on adsorption performance
[0093] (1) Comparison of adsorption properties of different modified materials
[0094] In order to verify that the DES-functional MMIL-101-NH2 has excellent adsorption performance, the adsorption of tetracycline by each step of the synthesis was investigated and compared. 100.0 mL of tetracycline with a concentration of 200.0 μg / mL was prepared. 2.0 mg of Fe3O4, MIL-101-NH2, MMIL-101-NH2, and MMIL-101-NH2-DES were weighed in 4.0 mL of tetracycline solution, and each material was prepared in triplicate. The mixture was ultrasonicated at room temperature for 2 h and then separated by an external magnetic field. The supernatant was taken and analyzed by HPLC to determine the tetracycline concentration in the supernatant. The adsorption capacity of different materials was calculated using formula (1).
[0095] (2) Adsorption isotherm
[0096] Tetracycline solutions with concentrations of 10.0, 25.0, 50.0, 100.0, 150.0, 200.0, 250.0, 300.0, 350.0, 400.0, 500.0, and 550.0 μg / mL were prepared with 0.01 M HCl, and 3.0 mg of MMIL-101-NH2-DES was accurately weighed. 4.0 mL of tetracycline solutions with different concentrations and pH 8.0 were added to MMIL-101-NH2-DES, and 3 replicates were measured for each concentration. The mixture was placed in an ultrasound chamber and ultrasound was performed at room temperature for 2 h, with water changed every 30 min. After removing the material with an external magnet, the supernatant was filtered through a 0.22 μm filter membrane and analyzed by HPLC. Then, the adsorption capacity was calculated by formula (3-1). At the same time, formula (2) and formula (3) can be used to determine whether the adsorption type belongs to the Langmuir isotherm model or the Freundlich isotherm model.
[0097] C e / Q e =C e / Q m +1 / (Q m K L )#(2)
[0098] ln(Q e )=nln(C e )+ln(K F )#(3)
[0099] Among them C e is the solution concentration at adsorption equilibrium, Q e (mg / g) is the adsorption capacity at adsorption equilibrium, Q m (mg / g) is the theoretical maximum adsorption capacity. L (L / m) is the Langmuir adsorption constant, which is related to the affinity of the binding site.F ((mg / g)(L / mg) n ) is the Freundlich model constant, which can be used to describe the adsorption performance of the adsorbent. n is the surface heterogeneity coefficient. The closer the n value is to zero, the more uneven the binding site affinity is.
[0100] (3) Adsorption kinetics
[0101] 3.0 mg of MMIL-101-NH2-DES was added to 4.0 mL of tetracycline solution with a concentration of 400.0 μg / mL and a pH of 8.0, and placed in an ultrasound for different times (0-180 min). After removing the material with an external magnet, the supernatant was filtered through a 0.22 μm filter membrane and analyzed by HPLC. Then, the adsorption capacity was calculated by formula (1). And the constants in formulas (4) and (5) were used to determine whether the adsorption kinetics type belongs to the pseudo-first-order model or the pseudo-second-order model.
[0102] ln(Q e -Q t )=lnQ e -K1t#(4)
[0103] t / Q t =t / Q e +1 / (K2Q e 2 )#(5)
[0104] Among them, Q e and Q t (μg / mL) represents the adsorption amount of tetracycline by the material at adsorption equilibrium and at t (min), respectively; t (min) is the adsorption time; K1 and K2 represent the rate constants of pseudo-first-order and pseudo-second-order kinetics, respectively.
[0105] 5. Research on anti-interference ability and selectivity
[0106] In the actual environment where tetracycline may exist, such as water environment, there are multiple co-ions, which may affect the adsorption process of tetracycline. 2+ , Cl - 、NO 3- and SO4 2-They are commonly found in the actual environment, and MMIL-101-NH2-DES may be adsorbed through electrostatic interactions. They are selected as coexisting ions to study the effect of ions on tetracycline adsorption. Weigh 3.0 mg of MMIL-101-NH2-DES and add them to 4.0 mL, 100.0 μg / mL of tetracycline in sequence. The concentration of each coexisting ion in the adsorption system is 9.1 mmol / L. The mixture is placed in ultrasound and ultrasound is performed at room temperature for 2 hours. After the adsorption is completed, the material is separated from the supernatant by applying an external magnetic field, and the supernatant is taken for HPLC analysis to determine the concentration of the drug in the supernatant.
[0107] Adsorption selectivity experiments can be used to evaluate the selectivity of MMIL-101-NH2-DES materials. Common antibiotics in sewage were selected, oxytetracycline was used as a structural analogue, and norfloxacin, levofloxacin, sulfadiazine and sulfamethoxazole were used as structural non-analogues to study the selectivity of MMIL-101-NH2-DES. 3.0 mg of MMIL-101-NH2-DES was weighed and added to 4.0 mL, 150.0 μg mL -1 The adsorption conditions were kept the same.
[0108] 6. Adsorption of tetracycline in sewage
[0109] In order to evaluate the feasibility and practicality of this method, sewage was first used as a real sample (sewage was taken from the Wuhe County Sewage Plant in Bengbu City, Anhui Province) and tetracycline was used as a model analyte. The collected sewage samples were centrifuged at 10,000 rpm for 10 minutes and then filtered with a 0.22 μm filter membrane as the actual sample.
[0110] result
[0111] 1. Characterization of MMIL-101-NH2-DES
[0112] In order to prove the successful preparation of MMIL-101-NH2-DES, its optical properties and morphology composition were characterized by transmission electron microscopy (TEM), dynamic light scattering (DLS), EDS energy spectrum scanning, elemental analysis, X-ray diffraction (XRD), infrared absorption spectroscopy (FT-IR), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM), Zeta potential and specific surface area test (BET) to prove the successful synthesis.
[0113] (1) TEM morphology analysis and particle size analysis
[0114] The morphology and size of Fe3O4, MMIL-101-NH2 and MMIL-101-NH2-DES were observed by transmission electron microscopy and Malvern particle size analyzer, respectively, as shown in the figure. Figure 2 (A) and (D) show that Fe3O4 nanoparticles are spherical with an average diameter of about 55nm. Figure 2 (B) and (E) show that after MIL-101-NH2 grows with Fe3O4, the shape of the nanoparticles remains almost unchanged, the magnetic spheres are wrapped on the surface of MIL-101-NH2, and the roughness of the material increases slightly. Figure 2 (C) and (F) show that after DES modification, the particle size of the composite material increases slightly. The regular hexahedron is surrounded by a large number of small irregular particles, and the surface roughness is further increased. Figure 2 (G), (H) and (I) are the hydrated particle sizes of Fe3O4, MMIL-101-NH2 and MMIL-101-NH2-DES, respectively, and the results are consistent with those of TEM. All the conclusions prove that the synthesis of MMIL-101-DES composite material is successful.
[0115] (2) EDS element analysis
[0116] In order to further study the elemental composition, the C, H, and N content of the material was determined and EDS elemental analysis was performed. The elemental content of MMIL-101-NH2 and MMIL-101-NH2-DES is shown in Figure 1. It can be seen that after DES modification, the carbon content increased from 18.22% to 24.01%, and the hydrogen and nitrogen contents decreased slightly. DES is mainly composed of C and H elements. After modification, the ratio of H and N content to the total mass decreased, which is consistent with the experimental results, further proving that MMIL-101-NH2-DES was successfully synthesized. In addition, from Figure 3 It can be seen that there is no C element distribution in the external magnetic sphere, and the N, O, and Fe elements are evenly distributed in the material, which proves the uniformity of the synthetic material.
[0117] Table 1 Element contents of MMIL-101-NH2 and MMIL-101-NH2-DES
[0118]
[0119]
[0120] (3)XRD
[0121] The crystal structures of Fe3O4, MMIL-101-NH2 and MMIL-101-NH2-DES were confirmed by XRD. Figure 4(A) As shown. The peaks at 30.14°, 35.44°, 43.14°, 53.49°, 57.08° and 62.64° at 2θ correspond to the typical Fe3O4 cubic spinel structure. After the growth of MMIL-101-NH2, the newly appeared peaks at 8.42°, 10.21°, 16.37° and 17.91° are attributed to the (100), (011), (200) and (210) planes of the MMIL-101-NH2 single crystal, respectively, indicating that MMIL-101 was successfully grafted. In addition, the peak position of the diffraction peak did not change during the DES functionalization process, indicating that the synthesized material retains the crystal form of Fe3O4 and MIL-101-NH2.
[0122] (4) FI-IR
[0123] FT-IR spectroscopy was used to characterize the functional groups of the three nanoparticles, and the results are shown in Figure 4 (B) As shown. At 557cm -1 The peaks are attributed to the stretching vibration of Fe-O. The symmetric and asymmetric stretching vibrations of the -COO group in PSSMA appear at 1602 cm -1 and 1409cm -1 For MMIL-101-NH2, 3469 cm -1 and 3371cm -1 The peaks at 1656 cm represent the asymmetric and symmetric stretching vibrations of the NH group. -1 The peak at 1581 cm is attributed to the bending vibration of the NH group, while the peak at 1581 cm -1 and 1336cm -1 The bands correspond to the symmetric and asymmetric stretching vibrations of the -COO group. The retention of the original peak of Fe3O4 and the characteristic absorption peak of MIL-101-NH2 proves the successful synthesis of MMIL-101-NH2. In the FT-IR spectrum of MMIL-101-NH2-DES, the absorption peak of -NH2 disappears and disappears at 3367cm -1 、2968cm -1 and 2893cm -1 A new absorption peak appeared at , which was attributed to the stretching vibration of the -OH group and CH in DES, which further confirmed the successful grafting of DES.
[0124] (5)TGA
[0125] The thermal stability of Fe3O4, MMIL-101-NH2 and MMIL-101-NH2-DES was investigated by TGA. Figure 4(C) shows that in the temperature range of 30-800℃, the removal of water and excess solvent and the decomposition of surface-coordinated PSSMA will lead to a weight loss of about 13.68wt% of Fe3O4. The weight loss of MMIL-101-NH2 can be divided into four stages. In the first stage (30-89.9℃), the excess crystal water in MMIL-101-NH2 is removed, and the weight loss is 4.58wt%. In the second stage (89.9-292.2℃), PSSMA and 2-aminoterephthalic acid in the composite Fe3O4 begin to decompose, and the weight loss is 10.60wt%; in the third stage (292.2-492.4℃), 2-aminoterephthalic acid continues to decompose, and an exothermic peak appears at 471.1℃, and the weight loss is 16.16wt%; in the fourth stage (429.4-800℃), the structure of MMIL-101-NH2 completely disintegrates, and the weight loss is 17.88wt%. In the TGA curve of MMIL-101-NH2-DES, the weight loss is similar to that of MMIL-10-NH2 and is divided into four stages. The weight loss in the first stage (30-82.5℃) is higher than that of MMIL-101-NH2, which is 11.34wt%, which may be due to the decomposition of its surface-modified Thy-based DES. The weight loss in the subsequent stages is similar to that of MMIL-101-NH2, and the final total weight loss is slightly higher than that of MMIL-101-NH2.
[0126] (6) VSM
[0127] The magnetic properties of Fe3O4 and MMIL-101-HN2-DES nanomaterials were studied using VSM. Figure 4 (C) depicts the hysteresis loop, and the saturation magnetization value of Fe3O4 is 67.31emu / g. The saturation magnetization value of MMIL-101-NH2-DES is 30.08emu / g. Due to the successful coating of non-magnetic MIL-101-NH2 and DES, the saturation magnetic susceptibility is reduced by about half, but its strength is sufficient to respond sensitively to the magnetic field, and compared with other MIL-101-NH2 composite materials, the magnetic composite material synthesized by the present invention is significantly stronger than other literature reports. [12,13] Magnetic separation in solution can be seen in Figure 4 (D).
[0128] (7) Zeta
[0129] Using deionized water as dispersant, the Zeta potential of the materials in each step of the synthesis was investigated, such as Figure 4As shown in (E), the surface of Fe3O4 is coated with electronegative PSSMA, so the Zeta potential is negative. MIL-101-NH2 uses 2-aminoterephthalic acid containing -NH2 as a ligand, so the surface Zeta potential is positive. During the synthesis process, Fe3O4 grows with MIL-101-NH2, so the Zeta potential of MMIL-101-NH2 decreases, which is consistent with the expected results.
[0130] (8)BET
[0131] MIL-101-NH2 is a porous structure. When its surface is functionalized and modified specifically, it can increase the adsorption sites, which is of great significance for the selective adsorption of target compounds. The number and volume of pores on the surface of the material are important parameters for analyzing the material structure. Figure 5 (A) and (B) are the adsorption / desorption isotherms of N2 by MMIL-101-NH2 and MMIL-101-NH2-DES at 77K. When the P / P0 ratio is low (less than 0.19), the adsorption amount of N2 increases rapidly and the adsorption isotherm protrudes upward. When the P / P0 ratio is high (0.19---.4), the curve rises slowly and steadily. When 0.8>P / P0>0.4, the adsorption amount of the material continues to increase, and when P / P0>0.8, capillary condensation occurs and a hysteresis loop is formed. Therefore, the N2 adsorption curves of these two materials are consistent with the IV type adsorption isotherm, indicating that both materials have a microporous structure and are monolayer adsorption. Table 2 shows the specific surface area and total pore volume of MMIL-101-NH2 and MMIL-101-NH2-DES. The data show that after DES functionalization, the surface area of the composite material MMIL-101-NH2-DES (218.26 m 2 / g) is lower than that of the original material. This reduction may be due to the fact that DES molecules modify the surface of MMIL-101-NH2 and fill its pores, resulting in the loss of part of the surface area. However, the pore size of MMIL-101-NH2 has increased. The possible reason is that DES is a liquid, which blocks some microporous structures during the modification process, resulting in a larger pore size, indicating that DES has a certain pore expansion effect. Although the specific surface area of the functionalized MMIL-101-NH2-DES has been lost, the modification of DES has added many reaction sites to it, greatly improving the adsorption performance of the MMIL-101-NH2-DES composite material.
[0132] Table 2 Pore structure parameters of MMIL-101-NH2 and MMIL-101-NH2-DES
[0133]
[0134] 2. Optimization of MMIL-101-NH2-DES adsorption conditions
[0135] (1) Adsorbent dosage
[0136] The effect of different adsorbent dosages of MMIL-101-NH2-DES on the removal rate of tetracycline was studied. Figure 6 (A) shows that compared with the literature [1] ,It is worth noting that in 4.0mL of 100.0μg / mL solution, adding 3.0mg of adsorbent can achieve almost complete adsorption, and the removal rate is as high as about 98%.
[0137] (2) Adsorption temperature optimization
[0138] Temperature has a certain influence on the adsorption kinetics and dissociation degree of the target in the solution. Figure 6 As shown in (B), with the increase of temperature, the adsorption capacity of MMIL-101-NH2-DES gradually increased, but the difference was not large. Adhering to the concept of green development, high temperature is accompanied by high energy consumption, so the subsequent adsorption experiments were carried out at room temperature.
[0139] (3) Adsorption pH optimization
[0140] The pH value affects the existence form, corresponding density and charge type of the adsorption sites on the surface of MMIL-101-NH2-DES, thus affecting the adsorption effect. Tetracycline is an amphoteric compound with a pK a The pH value range is very wide (3-4, 7-8 and 9-10). a1 -pK a2 In the range of pH, it exists as a zwitterion with a neutral net charge, which is conducive to hydrophobic interaction. However, under acidic conditions (pH < 3), tetracycline is positively charged and will be converted into anhydrous tetracycline through a dehydration process. In alkaline media (pH > 8), tetracycline is negatively charged and its ring may be opened to form isotetracycline. Therefore, pH may have an effect on the adsorption of MMIL-101-NH2-DES, such as Figure 6 As shown in (C), with the increase of pH, the adsorption amount gradually increased and then tended to be flat. When the pH was 8.0, the adsorption amount was the largest, so the subsequent experiments were carried out under the condition of pH 8.0.
[0141] 3. Study on the adsorption performance of MMIL-101-NH2-DES
[0142] (1) Adsorption isotherm
[0143] To evaluate the adsorption performance of MMIL-101-NH2-DES, we plotted its adsorption isotherm, as shown in Figure 7(A). The results show that as the concentration of tetracycline increases, its adsorption capacity also increases accordingly. In particular, when the concentration of tetracycline reaches 400.00μg / mL, the adsorption capacity tends to be stable, about 484.56mg / g. When the concentration of tetracycline increases further, the adsorption amount basically does not change, indicating that the adsorption amount has reached the maximum and MMIL-101-NH2-DES reaches adsorption equilibrium. The adsorption process of MMIL-101-NH2-DES was fitted using the Langmuir (Formula 2) and Freundlich (Formula 3) models, and its maximum adsorption capacity was calculated according to the fitting equations. The fitting results are shown in Figure 2. Figure 7 (B) and (C), and the relevant parameters are summarized in Table 3. The maximum adsorption capacity of MMIL-101-NH2-DES calculated by the Langmuir isotherm model (507.61 mg / g) is not much different from the actual value (493.48 mg / g). In addition, the correlation coefficient R 2 The R value is 0.9948, which is significantly better than the Freundlich model. 2 (0.8197). Therefore, the adsorption behavior of MMIL-101-NH2-DES is more consistent with the Langmuir model, indicating that the adsorption is chemical adsorption and the adsorption process is exothermic. m The values show that the synthesized MMIL-101-NH2-DES has a higher adsorption capacity and better adsorption site affinity for tetracycline, and it is more suitable to use the Langmuir isotherm model to describe the adsorption behavior of MMIL-101-NH2-DES. It shows that the adsorption process is a monolayer adsorption and is uniformly adsorbed on the solid surface.
[0144] Table 3 Langmuir and Freundlich thermodynamic model parameters
[0145]
[0146]
[0147] (2) Adsorption kinetics
[0148] The adsorption kinetics of tetracycline by MMIL-101-NH2-DES is shown in Figure 7 (D) As shown. The results show that within 0-180min, the adsorption amount increased significantly with the increase of time, and the adsorption amount remained basically unchanged after 60min. In order to further study the adsorption performance, the present invention introduced the pseudo-first-order kinetic model and the pseudo-second-order kinetic model. The fitting results are shown in Figure 7 (E) and (F). Based on the adsorption kinetics data, the model parameters of the two equations were calculated according to formulas (4) and (5).e is the adsorption amount at equilibrium, Q t is the adsorption amount at different times, and t is the adsorption time. K1 and K2 are constants of the first-order and second-order kinetic models, and the relevant parameters calculated are shown in Table 4. Obviously, the maximum adsorption capacity (490.20 mg / g) calculated by the pseudo-second-order kinetic model is closer to the actual maximum adsorption capacity (493.48 mg / g). In addition, the correlation coefficient R of the pseudo-second-order kinetic model 2 (0.9934) is also much larger than the correlation coefficient R of the pseudo-first-order kinetic model. 2 (0.7322). Therefore, the pseudo-second-order kinetic model is more suitable for describing the adsorption process of MMIL-101-NH2-DES. In other words, chemical adsorption plays a dominant role in the adsorption process of tetracycline.
[0149] Table 4 Adsorption kinetic model parameters
[0150]
[0151] (3) Comparison of adsorption properties of different modified materials
[0152] In order to verify that DES-regulated MMIL-101-NH2 can improve the adsorption performance of tetracycline, the adsorption properties of different materials were studied, and the results are as follows: Figure 8 As shown. After MIL-101-NH2 was modified with magnetic spheres, the adsorption performance decreased, probably because the magnetic spheres occupied a part of the adsorption sites. However, after DES regulation, the adsorption performance of MMIL-101-NH2 was improved, which was significantly higher than MIL-101-NH2 and MMIL-101-NH2. The possible reason is that DES provides more adsorption sites for MMIL-101-NH2. According to the above adsorption performance research results, the adsorption behavior of the composite material follows the Langmuir isotherm model and the pseudo-second-order kinetic model. This shows that the composite material can bind to tetracycline through various chemical interactions such as hydrogen bonds and π-π conjugation, which explains its higher adsorption capacity. In addition, according to the literature, MOF regulated by DES can increase the adsorption sites of target molecules, thereby producing a synergistic effect with MOF materials. [2] The adsorption performance of MMIL-101-NH2-DES is not only better than that of a single adsorbent, but also has obvious advantages over other published adsorbents. For example, Yu et al. [3] The adsorption capacity of tetracycline using MIL-68(Al) / GO modified material is about 228 mg / g, which is lower than that of MMIL-101-NH2-DES. The adsorption capacity of some reported porous MOFs is even lower, only 49.3 mg / g. [4] .
[0153] 4. Study on the anti-interference ability and selectivity of MMIL-101-NH2-DES
[0154] (1) Anti-interference capability
[0155] Considering that the adsorption of tetracycline in actual water environment may be affected by a variety of co-ions, especially Na, K, Ca 2 + , Cl - 、NO 3- and SO4 2- These ions commonly present in the environment may affect the adsorption process of tetracycline through electrostatic interactions. Therefore, these ions were selected as coexisting ions for research, aiming to explore their specific effects on the adsorption of tetracycline by MMIL-101-NH2-DES. The concentration of each coexisting ion in the adsorption system was 9.1mmol / L, and other adsorption conditions remained unchanged. Fig. 9 The results shown in (A) indicate that the coexisting ions have no significant effect on the adsorption of tetracycline. 2+ The diameter is larger than Na + , which has a charge screening effect on the adsorption of tetracycline, may compete with tetracycline for adsorption, and slightly reduce the adsorption capacity of tetracycline. The above conclusions all prove that the coexisting ions have no serious negative impact on the adsorption of tetracycline by MMIL-101-NH2-DES, and can effectively remove tetracycline in complex environments.
[0156] In order to further investigate the selective adsorption of antibiotics by MMIL-101-NH2-DES, antibiotics that are widely used and enriched in trace amounts in water environments were selected. The present invention selected oxytetracycline (OT) as a structural analog of tetracycline, and norfloxacin (NOX), levofloxacin (FLE), and two sulfonamide drugs, sulfadiazine (SD) and sulfamethoxazole (SMZ), as structural non-analogs. The results are shown in Figure 2. Fig. 9 As shown in (B), MMIL-101-NH2-DES has a good adsorption capacity for tetracycline antibiotics. The present invention selects DES with selective adsorption for tetracycline antibiotics for modification. Therefore, the functionally modified MMIL-101-NH2-DES inherits a large specific surface area and unsaturated reaction sites, and retains the multiple reactive functional groups of DES, thereby improving the adsorption capacity while increasing the selectivity.
[0157] 5. Study on the adsorption mechanism of MMIL-101-NH2-DES
[0158] In-depth exploration of the adsorption mechanism can further explore the interaction between specific functional groups of the adsorbent and the target analyte, open up more possibilities for designing new and efficient adsorbents, and thus improve the performance of the adsorbent. According to adsorption kinetics, adsorption isotherm model and thermodynamic analysis, the adsorption of tetracycline by MMIL-101-NH2-DES is a monolayer adsorption. Chemical adsorption and physical adsorption are comprehensively considered, and chemical adsorption plays a major role. The present invention also speculates adsorption mechanisms such as electrostatic interaction, chelation, π-π stacking and hydrogen bonding, and further explores possible mechanisms.
[0159] (1) Coordination interaction
[0160] To further confirm the interaction, the FT-IR spectra of MMIL-101-NH2-DES before and after adsorption were also tested, such as Fig.10 (A) shows that at 3400-3600cm -1 The broad peak in the region is attributed to the stretching vibration of -OH, which becomes broader and weaker after adsorption, indicating that hydrogen bonding interactions play a role in adsorption, probably because the -OH of DES modified on the surface of MMIL-101-NH2-DES is replaced during the adsorption process. It is also observed that the bending vibration of CN is weakened after adsorption, indicating that -NH2 is also involved in the absorption of tetracycline. In addition, the aromatic CC at 1037cm -1 The absorption peak of tetracycline is enhanced, indicating that the π-π interaction between tetracycline and the material is also an important adsorption mechanism. After tetracycline adsorption, the Fe-O peak at 543 cm -1 The increase in the adsorption rate proves the existence of Fe-O during the adsorption process.
[0161] XPS analysis was performed on MMIL-101-NH2-DES before and after tetracycline adsorption to study the interaction between the adsorbent and tetracycline. Fig.10 Fe, C, N, and O elements were observed in (B), which is consistent with the EDS spectrum. Fig.10 As shown in (C), the peaks at 711.08 eV and 725.88 eV are attributed to the Fe 2p 3 / 2 and Fe 2p 1 / 2 . C 1s spectrum ( Fig.10 (D)) consists of 284.68eV, 288.58eV, 288.58eV and 292.88eV, which are attributed to CC, CO, C=O and aromatic C=O conjugated with (-COOH), respectively. N 1s spectrum ( Fig.10 (E)) The single peak at 399.68 eV is attributed to -NH or -NH2 groups. O1s spectrum ( Fig.10(E) shows that the peak at 532.78 eV is attributed to OC=O in PSSMA, and the peaks at 529.98 eV and 531.38 eV are attributed to Fe-O and Fe-OH in MIL-101-NH2, respectively. After adsorption of tetracycline, the binding energy of Fe 2p slightly shifts to a lower binding energy ( Fig.10 (C)), the decrease in the binding energy peak can be attributed to the charge transfer from oxygen (nitrogen) to Fe(III). The empty orbital of Fe(III) accepts electrons from the electron-rich group and forms a metal complex with the oxygen / nitrogen-containing functional group through coordination bonds. C 1s( Fig.10 In the (D) spectrum, all decomposed C1s peaks move toward higher binding energy. The decrease in the electron cloud density of the active carbon functional groups is one of the main reasons for this change, indicating that these active functional groups are involved in the adsorption of tetracycline by the three Fe-based MOFs. Therefore, there are hydrogen bonds and π-π interactions between MMIL-101-NH2-DES and tetracycline during the adsorption process. The disappearance of the carbon peak at 292.88 eV indicating π-π conjugation also proves this point of view. After adsorbing tetracycline, the N 1s characteristic peak ( Fig.10 (E)) decomposes into two independent peaks centered at 399.68eV and 402.18eV, which are attributed to -NH(NH2) and Fe-NC, and the binding energy shifts to higher binding energy values, which may be due to the formation of coordination bonds between the nitrogen-containing groups of tetracycline and the open metal sites of MOF. The O 1s spectrum (10(F)) shows that after the adsorption of tetracycline, the peaks at 529.98eV and 531.38eV shift to a slightly higher binding energy direction, indicating that the oxygen-containing groups of MMIL-101-NH2-DES are involved in the adsorption process of tetracycline.
[0162] (2) Electrostatic interaction
[0163] Tetracycline is an amphoteric compound. When the initial pH value of the solution is >7.7, the surface of tetracycline is negatively charged and can be adsorbed by the positively charged MMIL-101-NH2-DES. Therefore, electrostatic interactions may exist during the adsorption of tetracycline on the Fe-based MOF surface.
[0164] (3) Hydrogen bond interaction
[0165] The hydrogen bonding between DES modified on the surface of MMIL-101-NH2-DES and the oxygen / nitrogen-containing functional groups of tetracycline also led to the adsorption of tetracycline. The direction of hydrogen bonding can be inferred from the effect of pH on the adsorption amount. If tetracycline is a hydrogen bond donor, the adsorption amount will decrease significantly with increasing pH because the tetracycline molecule carries more negative charges in this case. However, the adsorption amount increases (maximum at pH = 8.0); therefore, tetracycline is not a hydrogen bond donor, and the DES group on the Fe-based MOF should be considered as a hydrogen bond donor. Compared with other adsorption interactions, hydrogen bonding is not the main adsorption interaction.
[0166] 6. Reusability
[0167] The reusability of MMIL-101-NH2-DES is an important indicator for determining the practicality of an adsorbent in industrial applications, as a high number of cycles can greatly save costs. Tetracycline adsorbed on MMIL-101-NH2-DES was sonicated in PB buffer at pH 3.0 for 2 h and then centrifuged to obtain the regenerated adsorbent. The results are shown in Fig.11 As shown, the material still has an adsorption capacity of more than 85% after 5 consecutive adsorption-desorption cycles, indicating that the MMIL-101-NH2-DES material has excellent recyclability.
[0168] 7. Application
[0169] Prior to this, the adsorption performance of the adsorbent on tetracycline solution was studied and the adsorption conditions were optimized. In order to further prove that MMIL-101-NH2-DES has a strong adsorption effect on tetracycline and is suitable as a solid phase extraction agent, it was applied to enrich tetracycline in real samples (sewage). After testing, there was no tetracycline in the sewage, so a certain concentration of tetracycline was added to the sewage. Fig.12 As shown, almost all tetracycline in sewage can be adsorbed by MMIL-101-NH2-DES.
[0170] 8. Comparison with other methods
[0171] The proposed method for adsorbing tetracycline based on MMIL-101-NH2-DES adsorbent was compared with the reported methods. Detailed data are shown in Table 5. By comparison, it can be found that the adsorption capacity of some non-magnetic MOFs or carbon-based materials with relatively large specific surface areas is greater than that of the method developed in this paper, but the gap is not very large. At the same time, compared with some magnetic MOFs, the MOF synthesized by the present invention has excellent magnetic properties and the adsorption of tetracycline is also much greater than other reported magnetic MOFs. In addition, the present invention only needs 3.0 mg of adsorbent to obtain satisfactory tetracycline removal ability in tetracycline solutions with high concentration (100.0 μg / mL) and large volume (4.0 mL). In addition, the introduction of magnetic iron oxide in the base material effectively improves the convenience of the sample pretreatment process. In summary, the comparison results show that the proposed tetracycline removal method has the advantages of simple adsorption process, large adsorption capacity, environmental friendliness, and sustainability. In general, it has a large adsorption capacity and strong magnetism, and has good application prospects in the removal of tetracycline in the environment.
[0172] Table 5 Comparison of magnetic properties of different adsorbents and their adsorption capacity for tetracycline
[0173]
[0174] References
[0175] [1]Rafiq K,Tofazzal Hossain M,Ahmed R,et al.Role of Different GrowthEnhancers as Alternative to In-feed Antibiotics in Poultry Industry[J].Frontiers in Veterinary Science,2021,8:794588.
[0176] [2]Scaria J,Anupama KV,Nidheesh PV.Tetracyclines in the environment:An overview on the occurrence,fate,toxicity,detection,removal methods,andsludge management[J].Science of the Total Environment,2021,771:145291.
[0177] [3]Zhou LJ,Ying GG,Zhao JL,et al.Trends in the occurrence of humanand veterinary antibiotics in the sediments ofthe Yellow River,Hai River andLiao River in northern China[J].Environmental Pollution,2011,159(7):1877-1885.
[0178] [4]Deblonde T,Cossu-Leguille C,Hartemann P.Emerging pollutants inwastewater:a review of the literature[J].International Journal of Hygiene andEnvironmental Health,2011,214(6):442-448.
[0179] [5]Pan L,Peng Z,Yu H,et al.Robust synthesis of highly chargedsuperparamagnetic Fe3O4 colloidal nanocrystal clusters for magneticallyresponsive photonic crystals[J].New Journal of Chemistry,2021,45(36):16511-16519.
[0180] [6]Li M,Yuan G,Zeng Y,et al.Efficient removal of Co(II)from aqueoussolution by flexible metal-organic framework membranes[J].Journal ofMolecularLiquids,2021,324:114718.
[0181] [7]Zhang J,Wu T,Chen S,et al.Versatile structure-directing rolesofdeep-eutectic solvents and their implication in the generation ofporosityand open metal sites for gas storage[J].Angewandte Chemie InternationalEdition in English,2009,48(19):3486-3490.
[0182] [8]Sereshti H,Zarei-Hosseinabadi M,Soltani S,et al.Green vortex-assisted emulsification microextraction using a ternary deep eutectic solventfor extraction of tetracyclines in infant formulas[J].Food Chemistry,2022,396:133743.
[0183] [9]Dong Y,Hu T,Pudukudy M,et al.Influence of microwave-assistedsynthesis on the structural and textural properties of mesoporous MIL-101(Fe)and NH2-MIL-101(Fe)for enhanced tetracycline adsorption[J].MaterialsChemistry and Physics,2020,251:123060.
[0184]
[10] Zhang M-W,Lin K-YA,Huang C-F,et al.Enhanced degradation oftoxicazo dye,amaranth,in water using Oxone catalyzed by MIL-101-NH2 under visiblelight irradiation[J].Separation and Purification Technology,2019,227:115632.
[0185]
[11] Zhao D,Liu J,Zhou Y,et al.Penetrating the Blood-Brain Barrier forTargeted Treatment of Neurotoxicant Poisoning by Nanosustained-Released 2-PAM@VB1-MIL-101-NH2(Fe)[J].ACS Applied Materials&Interfaces,2023,15(10):12631-12642.
[0186]
[12] Wei X,Wang Y,Chen J,et al.Adsorption ofpharmaceuticals andpersonal care products by deep eutectic solvents-regulated magnetic metal-organic framework adsorbents:Performance and mechanism[J].ChemicalEngineering Journal,2020,392:124808.
[0187]
[13] Zhou X,Yin SJ,Chen GY,et al.Preparation of magnetic metal-organicframework MIL-101(Fe)and its application in the extraction of anthraquinonesin rhubarb[J].Journal of Separation Science,2022,45(13):2262-2272.
Claims
1. A magnetic metal organic framework regulated by a deep eutectic solvent, characterized in that: Prepared as follows: (1) Preparation of deep eutectic solvent DES Thymol, ethylene glycol and benzyl alcohol were mixed in a molar ratio of 2:2:1, and heated in an oil bath at 80°C for 0.5-2h until a homogeneous clear liquid was formed to obtain DES; (2) Preparation of Fe3O4@PSSMA FeCl3, ethylene glycol, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, and D-ascorbic acid were added in sequence and stirred, and then NaOH was added and stirred to form a mixture to react in a muffle furnace at 190°C to obtain Fe3O4@PSSMA; (3) Preparation of MMIL-101-NH2 Ultrasonic dispersion of Fe3O4@PSSMA and 2-aminoterephthalic acid in DMF; dissolution of FeCl3·6H2O in DMF; mixing the two and reacting them in a muffle furnace at 80-150°C to obtain MMIL-101-NH2; (4) Synthesis of MMIL-101-NH2-DES MMIL-101-NH2 was dispersed in DES methanol and ultrasonically treated to obtain the deep eutectic solvent-regulated magnetic metal-organic framework MMIL-101-NH2-DES.
2. The deep eutectic solvent-regulated magnetic metal organic framework according to claim 1, characterized in that: Prepared as follows: (1) Preparation of DES Thymol, ethylene glycol and benzyl alcohol were mixed in a molar ratio of 2:2:1, and heated in an oil bath at 80°C for 0.5-2h until a homogeneous clear liquid was formed to obtain DES; (2) Preparation of Fe3O4@PSSMA 0.4-0.9g FeCl3, 20-60mL ethylene glycol, 2-4g sodium acetate, 0.7-1.5g poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, 10-20mg D-ascorbic acid were added in sequence, and stirred for 20-60min to form a uniform mixture; then 0.4-0.8g NaOH was added and stirred for 1-2h until NaOH was completely dissolved; then the whole mixture was reacted in a muffle furnace at 190°C for 6-10h. After cooling to room temperature, the precipitate was washed three times with 10-50mL 50% V / V ethanol aqueous solution, and then washed three times with deionized water to obtain Fe3O4@PSSMA, referred to as Fe3O4; (3) Preparation of MMIL-101-NH2 0.2-0.4g Fe3O4@PSSMA and 0.2-0.4g 2-aminoterephthalic acid were ultrasonically treated for 5-20min and redispersed in 10-40mL DMF; thereafter, 0.5-1.5g FeCl3·6H2O was dissolved in 5-20mL DMF and ultrasonically treated for 10-30min; the two were then mixed and reacted in a muffle furnace at 110°C for 12-36h; after cooling to room temperature, the precipitate was washed several times with DMF and methanol, and then vacuum dried at 60°C for 24h to obtain MMIL-101-NH2. (4) Synthesis of MMIL-101-NH2-DES 100-300 mg MMIL-101-NH2 was dispersed in 10-40 mL methanol containing 2-6 mL DES and ultrasonicated for 1-3 h. The precipitate was washed several times with deionized water and then vacuum dried at 60 °C for 24 h to obtain the deep eutectic solvent-regulated magnetic metal organic framework MMIL-101-NH2-DES.
3. Use of the magnetic metal organic framework regulated by the deep eutectic solvent according to claim 1 or 2 as an adsorbent to adsorb tetracycline.
